Antidiabetic and Hypolipidemic Activities of Curculigo Latifolia Fruit : Root Extract in High Fat Fed Diet and Low Dose STZ Induced Diabetic Rats - Siti Aisyah Abd Ghafar; Nur Akmal Ishak; Maznah Ismail; Muhajir Hamid; Zalinah Ahmad (Hindawi, 2024)
Hindawi Publishing Corporation Evidence-Based Complementary and Alternative Medicine Volume 2013, Article ID 601838, 12 pages